SPECTROSCOPIC CLASSIFICATION OF CONFORMANCE WITH DIETARY RESTRICTIONS - HSIUNG CHANGMENG; O'BRIEN NADA A (2021)
A device can receive a classification model generated based on a set of spectroscopic measurements performed by a first spectrometer. The device can store a classification model in a data structure. The device can receive the spectroscopic measurement of an unknown sample from a second spectrometer. The device can obtain the classification model from the data structure. The device can classify the unknown sample into a kosher group or a non-kosher group or a halal group or a non-halal group based on the spectroscopic measurement and the classification model. The device can provide information of identifying the unknown sample based on classification of the unknown sample. 장치는 제1 분광계에 의해 수행된 분광 측정들의 세트에 기초하여 생성된 분류 모델을 수신할 수 있다. 상기 장치는 분류 모델을 데이터 구조 내에 저장할 수 있다. 상기 장치는 제2 분광계로부터의 미지의 샘플의 분광 측정을 수신할 수 있다. 상기 장치는 데이터 구조로부터 분류 모델을 취득할 수 있다. 상기 장치는 분광 측정 및 분류 모델에 기초하여 미지의 샘플을 코셔나 비코셔 그룹 또는 할랄이나 비할랄 그룹으로 분류할 수 있다. 상기 장치는 미지의 샘플의 분류에 기초하여 미지의 샘플을 식별하는 정보를 제공할 수 있다.